Implementation of Teachers’ Pedagogy in Developing Basic Competence in Subject that Contain Metacognitive - Siti Annisa Wahdiniawati; Wulan Sari; Tukiyo Tukiyo; Tuti Puspitasari; Dini Pepilina (Journal on Education, 2023)
This study aims to find out how the application of teacher pedagogy influences the development of basic biology competencies that contain metacognitive elements. The subjects of this study were teachers and students from schools A and B. The selection of subjects was based on differences in school admissions. The research method used is descriptive research. The results of this study indicate that the pedagogical implementation of teachers A and B is equally high in directing motives. Teacher A focuses more on interactions that occur between fellow students, and teacher B focuses more on interactions between teachers and students. The results of this study indicate that based on the mapping of class interactions according to the Verbal Category Interaction System, school A has the highest frequency of 28.3% occurring during group discussion activities. In school B, it has the highest frequency of 20.1%, which occurs during group discussions and presentations. Student B's metacognitive knowledge is better able to demonstrate metacognitive knowledge than student A.